PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INTERAKTIF BERBASIS CANVA PADA MATERI BANGUN DATAR DI SEKOLAH DASAR DENGAN PENDEKATAN TEORI BRUNER. - Dhela Fatimatul Azzahra; Nadiya Novita Sari; Nida Maulida Ridwana; Alfiana Nurussama; Teten Ginanjar Rahayu (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the feasibility and practicality of the Ca-Badar (Canva Plane Figures) learning media on plane geometry material for fourth-grade elementary school students. The feasibility of the media was evaluated based on assessments from media experts and subject matter experts, while its practicality was examined based on students’ responses. The Ca-Badar media was developed by integrating the principles of Bruner’s Theory, which include the enactive, iconic, and symbolic stages. The development process employed the ADDIE model, consisting of the analysis, design, development, implementation, and evaluation stages. The Ca-Badar media contains plane geometry materials, activities for matching the characteristics of plane figures, educational videos, interactive quizzes, and a creative project in the form of constructing a house using plane figures by utilizing Canva elements. The validation results from media experts and subject matter experts indicate that the Ca-Badar media falls into the highly valid and feasible category, with an average assessment score of 94.16%. The implementation of the media with 28 fourth-grade students at SDN 5 Sindangkasih shows that Ca-Badar is practical to use through laptops and projectors and is able to encourage student engagement and understanding during the learning process. In addition, the subject matter expert assessment resulted in an average score of 81%, which confirms the feasibility of the media as a learning tool for mathematics in elementary schools. The impact of this study is the availability of a feasible and practical digital learning media that can be used by teachers as an alternative for presenting plane geometry material, as well as a reference for the development of innovative Canva-based learning media in elementary schools.